POSTEXPERIMENTAL AND POSTMODERN: A TREATISE ON THE TRANSFORMATION AND THE NEW ROLE OF THE AVANT-GARDE LITERARY- LINGUISTC EXPERIMENT (Philological Studies, 2019)
Taking as its starting point a main thesis from the essay “tribut an die tradition. aspekte einer postexperimentellen literatur” (1975), written by Reinhard Priessnitz and Mechthild Rausch, this paper explores the transforming role of experimentalism in avant-garde, postmodern, and contemporary literary production. After historical avant-gardes and neo-avant-gardes innovatively applied various experimental linguistic techniques, post-experimental literature, a succeeding formation, appears as a writing practice which incorporates pre-existing experimental methods while using them merely as an instrument of traditional narrative forms. Therefore, post-experimentalism can be understood as a synonym for postmodernism (the term which Priessnitz and Rausch were not familiar with at the time of writing their essay), if the poetics of postmodernism would be analogously defined as a synthesis of avant-garde experiment and conventional narrative and genre forms. Thus, in both terms “post-experimental” and “postmodern” prefix post has the same role, denoting the weakening of previously radical modernist and avant-garde positions. Although not completely abolished or abandoned, experimentalism no longer has its original avant-garde autonomy, but is rather subordinated to classical literary instances such as plot or characterization. Consequently, the question “Who will take over: experimentally innovative or the traditional?” becomes almost an ethical and political issue – a question of politics of literature.
Keywords: post-experimental literature, postmodernism, language experiment, historical avant-gardes, neo-avant-gardes